Alpha-gal syndrome: when treatment of hypovolemic shock can lead to anaphylaxis - Nalin, Francesca; Scarmozzino, Rocco; Arcolaci, Alessandra; Olivieri, Bianca; Tommasi, Marina; Bonadonna, Patrizia; Zanoni, Giovanna (Allergologia et Immunopathologia, 2024)
Delayed anaphylaxis after ingestion of red meat because of galactose-alpha-1,3-galactose (alpha-gal) syndrome has increased in recent years. The mechanism involves an immunoglobulin E reaction to alpha-gal, a molecule found in mammalian meat, dairy products, medications and excipients containing mammalian-derived components, and tick salivary glycans. Sensitization occurs due to the bite of a lone star tick and the transmission of alpha-gal molecules into person's bloodstream. We describe a case of alpha-gal syndrome with severe food, drug, and perioperative allergy in which anaphylaxis with hypovolemic shock occurred immediately after an emergency surgical procedure, when a gelatin-containing drug was injected. This case study confirms that the clinical manifestations of alpha-gal syndrome could be different depending on the route of administration, with immediate reactions if an alpha-gal-containing drug is injected and delayed type allergic manifestations occurring several hours after oral intake. The purpose of this report is to highlight the importance of risk communication in case of exposure to medical products and surgical procedures of patients with alpha-gal syndrome and to encourage drug manufacturers to indicate clearly the origin of excipients in product literature.